Mediatisasi Hadis Melalui Musik sebagai Sarana Dakwah dalam Kanal Youtube Gontor TV - Reza, Raja Fahrul; Irfan, Irfan (Al-Qudwah, 2024)
This article discusses the phenomenon of the mediatization of Hadith as a means of Islamic preaching (dakwah) in the digital era, focusing on the Gontor TV YouTube channel as a case study. Gontor TV upholds the values embedded in the principles, motto, and “panca jiwa” of pesantren, ensuring that its preaching is educational, informative, and persuasive. This media channel contributes significantly to spreading Islamic teachings through various creative content, one of which is music. The message in this music is sourced from sacred texts, namely the Qur'an and the Hadith of the Prophet. This article is qualitative research using a descriptive qualitative approach and applying content analysis to examine the mediatization of Hadith as preaching content delivered through music on the Gontor TV YouTube channel. The research shows that the Hadith presented in the lyrics and music videos are displayed in various forms, such as excerpts from the matn without the complete isnad, sometimes including the mukharrij and its translation. These excerpts are then inserted into the lyrics, at the beginning or end of the music video, either in Arabic or Latin script. The Hadith are read textually, as there is no use of Hadith or other elements requiring contextual reading. Preaching through music on this YouTube channel has important implications in modern, multicultural, and heterogeneous societies, such as strengthening the internalization of religious messages, influencing the characteristics of musicians, increasing interest in music with Islamic nuances, being a form of creative and innovative dakwah, fostering interactions that strengthen religious life and Islamic identity, and serving as a medium for transmitting religious messages.Abstrak: Tulisan ini membahas tentang fenomena mediatisasi hadis sebagai sarana dakwah di era digital dengan mengambil objek kajian pada kanal Youtube Gontor TV. Gontor TV menjunjung tinggi nilai-nilai yang tertuang di dalam prinsip, motto, dan panca jiwa kepesantrenan sehingga penyajian dakwahnya harus memiliki sifat edukatif, informatif dan persuatif. Media ini ikut berkontribusi besar dalam mendakwahkan ajaran-ajaran Islam yang disampaikan melalui berbagai konten-konten kreatif, salah satunya musik. Pesan dari musik tersebut bersumber dari teks suci yaitu Al-Qur’an dan hadis Nabi. Tulisan ini merupakan jenis penelitian kualitatif (studi pustaka) dengan pendekatan deskriptif kualitatif dan menerapkan metode analisis konten dalam menganalisis mediatisasi hadis sebagai konten dakwah yang disampaikan melalui musik sebagai bajunya di kanal Youtube Gontor TV. Penelitian ini menunjukkan bahwa hadis-hadis yang tersaji dalam lirik musik dan video klip tersebut ditampilkan dalam berbagai bentuk seperti, potongan matan, tanpa sanad lengkap, terkadang menyertakan mukharrij dan terjemahannya. Potongan matan tersebut kemudian disisipkan dalam liriknya, di awal atau akhir video klip dengan tulisan Arab ataupun latinnya. Hadis-hadis tersebut dibaca secara tekstual, dikarenakan tidak ada penggunaan hadis atau lainnya yang mengharuskan pembacaan secara kontekstual. Dakwah dengan musik di kanal Youtube ini memilik implikasi yang penting di tengah masyarakat modern, multikultural dan heterogen seperti; menguatkan penjiwaan makna terhadap pesan agama, mempengaruhi karakteristik musisi, meningkatkan minat kepada musik dengan nuansa Islami, salah satu bentuk dakwah kreatif dan inovatif, interaksi yang memperkuat kehidupan beragama dan identitas ke-Islaman, serta sarana transmisi pesan agama.